Development of Myob Accounting Computer Teaching Materials at A Web-Based Service Company (Universitas Negeri Semarang, 2022)
The purpose of this study is to find out how the development of MYOB accounting computer teaching materials in web-based service companies that are valid, practical, and effectively used in computerized accounting learning to improve students' skills in operating MYOB accounting computers. This development research produces products in the form of MYOB accounting computer teaching materials at web-based service companies which are developed with a 4-D model into 4 stages, namely defining, designing, developing, and disseminating. Based on the validation results by validators, the feasibility of teaching materials is wonderful and the average reliability of all validators with reliable categories is so that teaching materials are worthy of use in learning. The form of innovation in learning resources and the learning approach provides a positive response to students, the results of student responses to teaching materials obtained from all aspects of MYOB accounting computer teaching materials at web-based service companies are marvelous. Students' skills in operating MYOB accounting computers differ between the control class and the experimental class, meaning that teaching material products have proven to be effectively applied in computerized learning of accounting, where the improvement of students' skills in operating MYOB accounting computers in the experimental class was obtained by a score of 0.322 with a moderate category.